Age-Related Impairment of Innate and Adaptive Immune Responses Exacerbates Herpes Simplex Viral Infection - Ruchi Srivastava; Sweta Karan; Yassir Lekbach; Afshana Quadiri; Ava Tohidian; Chhaya Maurya; Sarah Xue Le Ng; Reilly Chow; America Garcia; Anshu Agrawal; Hawa Vahed; Aziz A. Chentoufi; et al. (Pathogens)
Immune function declines with age, leading to increased vulnerability of the elderly to viral infectious pathogens. The mechanisms by which aging negatively impacts the innate and adaptive immune system, leading to enhanced susceptibility to respiratory viral pathogens, remain incompletely understood. In the present study, we utilized a mouse model of infection with herpes simplex virus type 1 (HSV-1), a virus that can infect the lungs and lead to pneumonia, a rare but serious health concern in the elderly. Following intranasal inoculation of young (6 weeks), adult (36 weeks), and aged mice (68 weeks) with HSV-1 (KOS strain) we: (i) compared the local and systemic immune responses to infection in young, adult, and aged mice, and (ii) correlated the level and type of immune responses to protection against HSV-1 infection and disease. Compared to young and adult mice, aged mice displayed: (i) increased activation of epithelial cells with a decreased expression of TLR3; (ii) increased activation of dendritic cells with increased expression of MHC-I, MHC-II, and CD80/86; (iii) decreased production of type-I interferons; (iv) delayed production of anti-inflammatory cytokines and chemokines in the lungs; and (v) impairment frequencies of functional HSV-specific CD107+IFN-γ+CD8+ T cells associated with the increased incidence of viral infection and disease. These findings suggest that age-related impairments in innate and adaptive immune responses may exacerbate respiratory viral infections and disease in the elderly.